Current collector, secondary battery, and electric device

By sequentially setting the inorganic sol layer and the carbon material conductive layer on the current collector surface, the problem of high contact resistance between active materials and current collectors in the prior art is solved, the charging and discharging performance and conductivity of the secondary battery are improved, and the DC internal volume is reduced Obstacle.

CN119400873APending Publication Date: 2025-02-07HUIZHOU LIWINON ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411540843.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the contact resistance between the positive and negative electrode active materials and the current collector, affecting the charging and discharging performance of the secondary battery.

Method used

The sol layer and conductive layer are arranged in turn on the surface of the base layer of the current collector. The sol layer is composed of inorganic sol. The conductive layer contains dot-shaped structure carbon material and planar structure carbon material. By controlling the hierarchy structure and material ratio, the layer density and conductivity are optimized. Network channel.

Benefits of technology

It effectively reduces the contact resistance between the active material and the current collector, improves the adhesion of the active material and the conductivity of the secondary battery, and reduces the DC internal resistance (DCR) of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112754390000111
    Figure BDA0005112754390000111
  • Figure BDA0005112754390000121
    Figure BDA0005112754390000121
  • Figure BDA0005112754390000131
    Figure BDA0005112754390000131
Patent Text Reader

Abstract

The invention discloses a current collector, a secondary battery and an electric device, and belongs to the technical field of batteries, the current collector comprises a substrate layer, and a sol layer and a conductive layer which are sequentially arranged on at least one surface of the substrate layer; the sol layer comprises inorganic sol, and the inorganic sol comprises at least one of aluminum sol, silica sol, silicon-aluminum sol and phosphorus-aluminum sol; the conductive layer comprises a dotted structure carbon material and a planar structure carbon material. According to the current collector, the contact resistance between the active material and the current collector can be effectively reduced, the adhesive force of the active material is improved, and the DCR of the secondary battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a current collector, a secondary battery and an electrical device. Background Art

[0002] Secondary batteries are generally composed of four parts: pole pieces, diaphragms, electrolytes and outer shells; pole pieces usually include current collectors and active materials attached to the surface of current collectors. The current collectors are in contact with the active materials, which collect the current generated by the active materials and output large currents to the outside. Among them, the quality of the contact between the current collectors and the active materials is an important factor affecting the battery's charge and discharge performance.

[0003] The industry uses a current collector coated with a conductive layer to improve the contact between the current collector and the active material, thereby reducing the contact resistance between the positive and negative active materials and the current collector, and improving the adhesion between the two. Generally, aluminum foil is selected as the positive electrode current collector. Aluminum foil is made by rolling aluminum ingots through casting, hot rolling, cold rolling, foil rolling and other processes. After surface decontamination and oxidation layer removal, its surface shows scratches, micropores, pinholes, pits and other defects generated during the rolling process under the microscopic view. Directly coating the surface with a conductive layer can generally only cover the surface defects and make them difficult to detect, but it cannot really improve the micropores, pinholes and other defects of the aluminum foil itself.

[0004] In view of this, this application is filed. Summary of the invention

[0005] The purpose of the present application is to overcome the shortcomings of the prior art and provide a current collector, a secondary battery and an electrical device, which can effectively reduce the contact resistance between the active material and the current collector, improve the adhesion of the active material, and reduce the DCR of the secondary battery.

[0006] To achieve the above-mentioned object, the first aspect of the present application provides a current collector, comprising a substrate layer and a sol layer and a conductive layer sequentially arranged on at least one surface of the substrate layer;

[0007] The sol layer includes an inorganic sol, and the inorganic sol includes at least one of aluminum sol, silica sol, silica-alumina sol, and phospho-alumina sol;

[0008] The conductive layer includes a point-structured carbon material and a surface-structured carbon material.

[0009] As an implementation scheme of the present application, the surface density of the sol layer is G1, and the surface density of the conductive layer is G2, satisfying: 4≤G2 / G1≤8.

[0010] As an implementation scheme of the present application, the mass percentage of the point-structured carbon material in the conductive layer is H1, and the mass percentage of the planar-structured carbon material in the conductive layer is H2, satisfying: 0.05≤H2 / (H1+H2)≤0.15.

[0011] As an implementation scheme of the present application, at least one of the following (a) to (d) is satisfied:

[0012] (a) 0.1 g / m 2 ≤G1≤0.3g / m 2 ;

[0013] (b)0.5g / m 2 ≤G2≤2g / m 2 ;

[0014] (c) 40% ≤ H1 ≤ 50%;

[0015] (d)1%≤H2≤10%.

[0016] As an implementation scheme of the present application, at least one of the following (e) to (h) is satisfied:

[0017] (e) the average particle size of the inorganic sol is 1 to 50 nm;

[0018] (f) the thickness of the sol layer is 0.1 to 1 μm;

[0019] (g) the thickness of the conductive layer is 0.5 to 5 μm;

[0020] (h) The thickness of the base layer is 5 to 20 μm.

[0021] As an embodiment of the present application, the oil absorption value of the point-structured carbon material is ≥120 mL / g; and / or

[0022] The oil absorption value of the planar structure carbon material is ≥120 mL / g.

[0023] As an embodiment of the present application, the dot-structured carbon material includes at least one of conductive carbon black, Ketjen black, and acetylene black; and / or

[0024] The planar carbon material includes at least one of layered graphite and graphene.

[0025] The second aspect of the present application provides a method for preparing a current collector, comprising the following steps:

[0026] Applying the inorganic sol liquid on the surface of the substrate layer and drying it to form a sol layer;

[0027] Then, a conductive paste is applied to the sol layer and dried to form a conductive layer;

[0028] The conductive paste includes a point-structured carbon material and a surface-structured carbon material;

[0029] The content of the inorganic sol in the inorganic sol solution is 0.4-1%.

[0030] A third aspect of the present application provides a secondary battery, comprising the current collector described above.

[0031] A fourth aspect of the present application provides an electrical device, comprising the secondary battery described above.

[0032] The beneficial effects of the present application are as follows: the present application sequentially arranges a sol layer and a conductive layer on the surface of the current collector, and uses an inorganic sol as the sol layer. The inorganic sol can be firmly fixed and attached to the surface defects of the current collector, and a binding force can be formed between the inorganic sol particles, which can effectively improve the defects such as pinholes, micropores and pits on the surface of the substrate layer itself, improve the strength of the current collector, reduce the contact resistance between the active material (positive electrode active material and / or negative electrode active material) and the current collector, and improve the adhesion of the active material to the surface of the current collector. At the same time, the sol layer can also make the conductive layer and the substrate layer combine more fully, reducing the conductive layer and The contact resistance between the substrate layers; the conductive layer comprising the point-structured carbon material and the planar-structured carbon material, wherein the point-structured carbon material and the planar-structured carbon material can form a zero-dimensional and multi-dimensional composite structure to form a conductive network channel, and the alternating undulating spatial manner can not only better fit with the substrate layer, but also allow the active material layer to be more firmly embedded in the coating interface, while improving the electrode peeling force, it can also improve the electron transmission capacity of the active particle surface, reduce the charge transfer impedance, thereby improving the current collector conductivity, and effectively reducing the DCR (DC internal resistance, which refers to the resistance generated inside the battery when a DC current passes through) of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the SEM analysis of aluminum sol. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0035] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0036] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple range description features are provided, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0037] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0038] Unless otherwise specified, the components, raw materials or instruments used in the examples and comparative examples of the present application are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are of the same kind.

[0039] The embodiment of the present application provides a current collector, comprising a base layer and a sol layer and a conductive layer sequentially disposed on at least one surface of the base layer;

[0040] The sol layer includes an inorganic sol, and the inorganic sol includes at least one of aluminum sol, silica sol, silica-alumina sol, and phospho-alumina sol;

[0041] The conductive layer includes a point-structured carbon material and a surface-structured carbon material.

[0042] The present application sequentially arranges a sol layer and a conductive layer on the surface of the current collector, and uses an inorganic sol as the sol layer. The inorganic sol can be firmly fixed and attached to the surface defects of the current collector, and a binding force can be formed between the inorganic sol particles (for example, aluminum sol forms an aluminum-oxygen bond), which can effectively improve the defects such as pinholes, micropores and pits on the surface of the substrate layer itself, improve the strength of the current collector, reduce the contact resistance between the active material (positive electrode active material and / or negative electrode active material) and the current collector, and improve the adhesion of the active material on the surface of the current collector. At the same time, the sol layer can also make the conductive layer and the substrate layer The combination is more complete, reducing the contact resistance between the conductive layer and the substrate layer; the conductive layer comprising the point-structured carbon material and the planar-structured carbon material, wherein the point-structured carbon material and the planar-structured carbon material can form a zero-dimensional and multi-dimensional composite structure to form a conductive network channel, and the alternating undulating spatial manner can not only better fit with the substrate layer, but also allow the active material layer to be more firmly embedded in the coating interface, while improving the electrode stripping force, it can also improve the electron transmission capacity of the active particle surface, reduce the charge transfer impedance, thereby improving the collector conductivity, and effectively reducing the DCR of the secondary battery.

[0043] In one embodiment, the surface density of the sol layer is G1, and the surface density of the conductive layer is G2, satisfying: 4≤G2 / G1≤8, for example, it can be 4, 5, 6, 7, 8 or a range consisting of any two of these values. By controlling the surface density of the sol layer and the conductive layer within this range, the conductive layer and the substrate layer can be more fully combined, and the contact resistance between the substrate layer and the conductive layer can be more effectively reduced.

[0044] In one embodiment, the mass percentage of the point structure carbon material in the conductive layer is H1, and the mass percentage of the planar structure carbon material in the conductive layer is H2, satisfying: 0.05≤H2 / (H1+H2)≤0.15, for example, it can be 0.05, 0.06, 0.08, 0.1, 0.12, 0.15 or a range consisting of any two of these values. By controlling the mass percentage of the point structure carbon material and the planar structure carbon material in the conductive layer within this range, it is possible to promote better bonding between the conductive layer and the substrate layer, and to promote better embedding of the active material into the coating interface. While improving the electrode stripping force, it is also possible to improve the electron transmission capacity on the surface of the active particles and reduce the charge transfer impedance, thereby improving the electrode conductivity and reducing the battery DCR of the secondary battery.

[0045] In one embodiment, 0.1 g / m 2 ≤G1≤0.3g / m 2 , for example, it can be 0.1g / m 2 , 0.15g / m 2 , 0.2g / m 2 , 0.25g / m 2 , 0.3g / m 2 Or a range consisting of any two of the values ​​therein, especially when the surface density of the sol layer is within this range, it can more effectively improve the defects such as pinholes, micropores and pits on the surface of the substrate layer itself, improve the strength of the current collector, reduce the contact resistance between the active material and the current collector, improve the adhesion of the active material on the surface of the current collector, and improve the bonding force between the conductive layer and the substrate layer.

[0046] In one embodiment, 0.5 g / m 2 ≤G2≤2g / m 2 , for example, it can be 0.5g / m 2 , 0.6g / m 2 , 0.8g / m 2 , 1g / m 2 , 1.2g / m 2 , 1.4g / m 2 , 1.5g / m 2 , 1.6g / m 2 , 1.8g / m2 , 2g / m 2 Or a range consisting of any two of the values ​​therein, especially when the surface density of the conductive layer is within this range, it can better fit with the substrate layer, and can also allow the active material layer to be more firmly embedded in the coating interface. While improving the electrode peeling force, it can also improve the electron transmission capacity on the surface of the active particles and reduce the charge transfer impedance, thereby improving the conductivity of the current collector and effectively reducing the DCR of the secondary battery.

[0047] In one embodiment, 0.8 g / m 2 ≤G2≤1.6g / m 2 .

[0048] In one embodiment, 40%≤H1≤50%, for example, it can be 40%, 41%, 42%, 44%, 45%, 46%, 47.5%, 48%, 49%, 50% or a range consisting of any two of these values.

[0049] In one embodiment, 42.5%≤H1≤49%.

[0050] In one embodiment, 42.5%≤H1≤45%.

[0051] In one embodiment, 1%≤H2≤10%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of these values.

[0052] In one embodiment, 5%≤H2≤7.5%.

[0053] In one embodiment, the average particle size of the inorganic sol is 1 to 50 nm, for example, it can be 1 nm, 2 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm or a range consisting of any two of these values.

[0054] In one embodiment, the average particle size of the inorganic sol is 10 to 50 nm.

[0055] In one embodiment, the average particle size of the inorganic sol is 30 to 40 nm.

[0056] In one embodiment, the thickness of the sol layer is 0.1-1 μm.

[0057] In one embodiment, the thickness of the conductive layer is 0.5-5 μm.

[0058] In one embodiment, the base layer has a thickness of 5 to 20 μm.

[0059] In one embodiment, the oil absorption value of the point-structured carbon material is ≥120 mL / g.

[0060] In one embodiment, the oil absorption value of the planar structured carbon material is ≥120 mL / g.

[0061] By using point-structured carbon materials and surface-structured carbon materials with high oil absorption values, it is possible to promote the formation of denser and more difficult to destroy conductive network channels.

[0062] In one embodiment, the dot-structured carbon material includes at least one of conductive carbon black, Ketjen black, and acetylene black.

[0063] In one embodiment, the planar carbon material includes at least one of layered graphite and graphene.

[0064] In one embodiment, the base layer includes at least one of copper foil, aluminum foil, titanium foil, nickel foil, iron foil, and zinc foil.

[0065] In one embodiment, the base layer comprises aluminum foil. When the base layer comprises aluminum foil, the current collector is usually used as a positive electrode current collector.

[0066] In one embodiment, the base layer comprises copper foil. When the base layer comprises copper foil, the current collector is usually used as a negative electrode current collector.

[0067] In one embodiment, the conductive layer further includes a binder and a dispersant.

[0068] In one embodiment, the mass percentage of the binder in the conductive layer is 40-80%, for example, it can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or a range consisting of any two of these values.

[0069] In one embodiment, the mass percentage of the dispersant in the conductive layer is 4% to 20%, for example, it can be 4%, 5%, 6%, 8%, 10%, 12%, 15%, 18%, 20% or a range consisting of any two of these values.

[0070] An embodiment of the present application provides a method for preparing a current collector, comprising the following steps:

[0071] Applying the inorganic sol liquid on the surface of the substrate layer and drying it to form a sol layer;

[0072] Then, a conductive paste is applied to the sol layer and dried to form a conductive layer;

[0073] The conductive paste includes a point-structured carbon material and a surface-structured carbon material;

[0074] The content of the inorganic sol in the inorganic sol solution is 0.4-1%, for example, 0.4%, 0.6%, 0.8%, 1% or a range consisting of any two of these values.

[0075] In one embodiment, the coating rate is 30-50 m / min, for example, 30 m / min, 35 m / min, 40 m / min, 45 m / min, 50 m / min or a range consisting of any two values ​​therein.

[0076] In one embodiment, drying is carried out in an oven at a drying temperature of 80-110°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C or a range consisting of any two of these values.

[0077] In one embodiment, the conductive paste further includes a binder and a dispersant.

[0078] In one embodiment, the conductive paste further includes a solvent, and the solvent is preferably water.

[0079] An embodiment of the present application provides a secondary battery, including a current collector, wherein the current collector includes the current collector described above.

[0080] It can be understood that a secondary battery generally includes an electrode assembly and an electrolyte, the electrode assembly includes a positive electrode plate, a negative electrode plate and a separator, and the secondary battery mainly relies on the movement of metal ions between the positive electrode plate and the negative electrode plate through the separator to work, wherein at least one of the positive electrode plate and the negative electrode plate includes the current collector of the first aspect of the present application.

[0081] For the convenience of explanation, the following specific implementation manner is described in detail by taking a lithium-ion secondary battery as an example.

[0082] More specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector.

[0083] In the present application, the positive electrode current collector includes the current collector described above.

[0084] In one embodiment, the positive electrode active material can be selected from lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, nickel cobalt manganese oxide, nickel cobalt aluminum oxide, nickel manganese aluminum oxide, etc. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more.

[0085] In one embodiment, the positive electrode material layer further includes a conductive agent and a binder.

[0086] In one embodiment, the secondary battery further includes a negative electrode plate, wherein the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0087] In the present application, there is no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.

[0088] In one embodiment, the negative electrode current collector may include the current collector described above.

[0089] In one embodiment, the negative electrode active material can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithium titanate Li4Ti5O 12 , at least one of Li-Al alloy and metallic lithium.

[0090] In one embodiment, the negative electrode active material layer further includes a conductive agent and a binder.

[0091] In one embodiment, the type of the conductive agent mentioned in the present application is not limited, and any known conductive agent can be used.

[0092] In one embodiment, the conductive agent includes at least one of carbon materials such as acetylene black, needle coke, carbon nanotubes, and graphene.

[0093] In one embodiment, the type of adhesive mentioned in the present application is not limited, and any known adhesive can be used.

[0094] In one embodiment, the binder includes at least one of polyacrylic acid, polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, styrene-butadiene-styrene block copolymer or its hydride, ethylene-propylene-diene terpolymer, styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer, isotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, propylene-α-olefin copolymer, polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymer.

[0095] In one embodiment, the type of dispersant mentioned in the present application is not limited, and any known dispersant can be used.

[0096] In one embodiment, the dispersant includes at least one of methyl cellulose, carboxymethyl cellulose, ethyl cellulose, hydroxyethyl cellulose, cellulose acetate, cyanoethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, cellulose nitrate, cellulose acetate, cellulose acetate butyrate, and cellulose sulfonate.

[0097] In one embodiment, the separator includes a porous sheet or non-woven fabric having excellent liquid retention. The materials of the resin or glass fiber separator include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, and the like.

[0098] In one embodiment, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above-mentioned diaphragm can be used alone or in any combination.

[0099] In one embodiment, the secondary battery may include an outer package, which can be used to encapsulate the electrode assembly and the electrolyte.

[0100] In one embodiment, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be an aluminum-plastic film or plastic, etc. As the plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate can be listed.

[0101] In some embodiments, the secondary battery further comprises an electrolyte, and the type of the electrolyte is not specifically limited. The electrolyte comprises an electrolyte salt and an organic solvent, and the specific types of the electrolyte salt and the organic solvent are not specifically limited and can be selected according to actual needs.

[0102] In one embodiment, the organic solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).

[0103] In one embodiment, the organic solvent includes at least one cyclic carbonate and at least one chain carbonate. The cyclic carbonate includes at least one of EC, PC, and butylene carbonate. The chain carbonate includes at least one of DMC, DEC, and EMC.

[0104] In one embodiment, the mass ratio of the cyclic carbonate to the linear carbonate is 1:(1-4), for example, it can be 1:1, 1:2, 1:3, 1:4 or a range consisting of any two values ​​therein.

[0105] In one embodiment, the lithium salt includes but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bisoxalatoborate (LiBOB), lithium difluorooxalatoborate (LiODFB), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium fluoride (LiF), and lithium trifluoromethanesulfonate (LiCF3SO3). In some embodiments, the lithium salt is LiPF6.

[0106] In one embodiment, the concentration of lithium salt in the electrolyte can be 0.5-2 mol / L, for example, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L or a range consisting of any two of these values.

[0107] In some embodiments, the electrolyte may further include additives. The type of the additives is not particularly limited and may be film-forming additives for the positive electrode and / or negative electrode, or additives that can improve certain battery properties, such as additives that improve the high or low temperature performance of the battery.

[0108] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0109] An embodiment of the present application provides an electric device, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electric device.

[0110] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0111] The following examples are provided to facilitate understanding of the present application. These examples are not provided to limit the scope of the claims.

[0112] Example 1

[0113] A method for preparing a secondary battery comprises the following steps:

[0114] (1) Preparation of positive electrode sheet:

[0115] Prepare aluminum sol and perform SEM analysis on aluminum sol (brand: ZTL-CYLJ, manufacturer: Yangzhou Zhongtianli New Materials Co., Ltd.). Figure 1 As shown, the particle size of aluminum sol is between 30 and 45 nm;

[0116] Aluminum sol solution with a solid content of 0.8% was coated on both sides of 12 μm aluminum foil at a coating rate of 40 m / min, and dried in an oven at 80°C to form a sol layer with a thickness of 0.3 μm, which was called a precursor current collector;

[0117] 10 kg of conductive slurry was prepared by mixing 0.475 kg of conductive carbon black Super P-Li, 0.025 kg of conductive graphite SFG6, 0.4955 kg of polyacrylic acid (brand: GR-506, manufacturer: Hunan Gaorui Power Material Co., Ltd.), 0.0045 kg of CMC and water. The conductive slurry was coated on the sol layer by a gravure roller and dried in an oven to form a conductive layer with a thickness of 1 μm to obtain a current collector.

[0118] The oil absorption value of the conductive carbon black Super P-Li is 290 mL / 100 g, and the oil absorption value of the conductive graphite SFG6 is 180 mL / 100 g.

[0119] The positive electrode active materials of lithium iron phosphate, polyvinylidene fluoride, conductive carbon black and carbon nanotubes in a mass ratio of 97.5:1.2:0.7:0.6 are uniformly mixed and dispersed in N-methylpyrrolidone to prepare a positive electrode slurry, and the positive electrode slurry is coated on the surface of the aluminum foil current collector, and the positive electrode sheet is obtained after drying;

[0120] (2) Preparation of negative electrode sheet: Graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber (SBR) and conductive carbon black, which are negative electrode active materials in a mass ratio of 96.1:1.2:1.7:1, are uniformly mixed and dispersed in water to prepare a negative electrode slurry. The negative electrode slurry is coated on the surface of a copper foil current collector and dried to obtain a negative electrode sheet.

[0121] (3) Preparation of electrolyte: Ethylene carbonate EC, ethyl methyl carbonate EMC, and diethyl carbonate DEC are mixed in a mass ratio of 1:1:1 to obtain a mixed solvent. After mixing evenly, 1 mol / L lithium hexafluorophosphate is added to dissolve completely, and stirred evenly to obtain an electrolyte;

[0122] (4) Diaphragm: a conventional PE diaphragm in the art is used;

[0123] (5) Preparation of secondary batteries: The die-cut positive and negative electrode sheets and separators are stacked to form laminated cells, which are then welded, packaged, baked, injected, formed, sealed a second time, and divided into different capacities to obtain soft-pack secondary batteries.

[0124] Embodiments 2 to 5

[0125] Compared with Example 1, Examples 2 to 5 change the coating amount of the conductive paste, thereby changing the surface density G2, as shown in Table 1 for details.

[0126] Embodiment 6-7

[0127] Compared with Example 1, Examples 6 to 7 change the coating amount of the aluminum sol solution in Examples 2 to 5, thereby changing the surface density G1, as shown in Table 1 for details.

[0128] Embodiments 8 to 11

[0129] Compared with Example 1, Examples 8 to 11 change the average particle size of the aluminum sol, as shown in Table 1 for details.

[0130] Embodiments 12 to 15

[0131] Compared with Example 1, Examples 12 to 15 change the added amounts of conductive carbon black Super P-Li and conductive graphite SFG6 in the conductive paste, and further adjust H1 and H2, as shown in Table 1 for details.

[0132] Example 16

[0133] Compared with Example 1, Example 16 uses silica sol (brand: S515, manufacturer: Hubei Zhenghe Tiancheng Technology Co., Ltd.) to replace aluminum sol.

[0134] Comparative Example 1

[0135] Comparative Example 1 Compared with Example 1, Comparative Example 1 does not contain a sol layer.

[0136] Comparative Example 2

[0137] Comparative Example 2 Compared with Example 1, Comparative Example 2 does not contain a conductive layer.

[0138] Comparative Example 3

[0139] Compared with Example 1, Comparative Example 3 uses a polyvinyl alcohol solution (organosol) with a solid content of 0.8% to replace the aluminum sol solution.

[0140] Comparative Example 4

[0141] The difference between Comparative Example 4 and Example 1 is that the conductive paste of Comparative Example 4 does not contain conductive carbon black Super P-Li, and is replaced by an equal amount of conductive graphite SFG6.

[0142] Comparative Example 5

[0143] The difference between Comparative Example 5 and Example 1 is that the conductive paste of Comparative Example 5 does not contain conductive graphite SFG6, and is replaced by an equal amount of conductive carbon black Super P-Li.

[0144] Table 1

[0145]

[0146]

[0147] Test Case

[0148] Number of pinholes in the precursor current collector: CCD online pinhole test is used.

[0149] Positive electrode sheet resistance: Use Yuanneng two-probe resistance meter to measure the electrode sheet resistance.

[0150] Secondary battery DCR: pulse internal resistance power test.

[0151] The specific steps of the positive electrode peeling force test are as follows: (1) Cutting the electrode: Take the rolled positive electrode and cut the electrode with a knife die, with a length of 400mm and a width of 40mm; (2) Pasting and fixing the electrode: Take a flat thin steel plate with a length of about 250mm and a width of about 50mm; First, paste a strip of double-sided tape in the center of the steel plate (the length can be greater than the sample test length and the same width as the electrode), and smooth it with force to ensure that the double-sided tape is tightly attached to the center of the steel plate. Peel off the double-sided tape and attach the electrode to the tape. It is necessary to ensure that the electrode and the tape are matched and attached, otherwise the width of the test peeling force will change, the test value will be inaccurate, and the peeling curve will have jump points or waves; (3) Installation test: There are two upper and lower clamps on the tensile machine. Insert the steel plate with the electrode pasted and fixed into the lower clamp and fix it vertically; insert the electrode without glue into the upper clamp and fix it, so that the electrode pasted on the tape is 180° with the electrode fixed by the upper clamp. After fixing the test sample, first calibrate and reset, set the test width, the electrode peeling length to 120mm, the peeling speed to 50mm / min, and then start the test to obtain the peeling strength curve. Measure 5 samples and take the average value.

[0152] Table 2

[0153]

[0154] It can be seen from Table 2 that the current collector of the present invention can effectively reduce the contact resistance between the active material and the current collector, reduce the number of pinholes, improve the adhesion of the active material, and reduce the DCR of the secondary battery.

[0155] By comparing Examples 1-5 and Comparative Examples 1, 2, 4, and 5, it can be seen that the combination of the conductive layer and the adhesive layer can reduce the resistance of the positive electrode sheet, thereby reducing the DCR of the battery, especially when 4≤G2 / G1≤8, the effect is more obvious, among which 0.1g / m 2 ≤G1≤0.3g / m 2 ; 0.5g / m 2 ≤G2≤2g / m 2 .

[0156] By comparing Examples 1, 6, and 7 with Comparative Example 1, it can be seen that coating an inorganic adhesive layer on the aluminum foil current collector has a repairing function for pinholes, taking into account the electrode resistance, and the double-sided surface density is 0.2 g / m 2 More suitable.

[0157] By comparing Examples 1, 8, 9, 10 and 11, it can be seen that when the particle size of the aluminum sol is smaller, the pinhole repair effect is better, and there is little difference in the range of 10-40 nm.

[0158] By comparing Examples 1, 12-15 and Comparative Examples 4 and 5, it can be seen that the point-shaped carbon material H1 and the surface-shaped carbon material H2 are compounded in a certain proportion, and have a zero-dimensional and multi-dimensional composite structure. The alternating undulating spatial structure can make the active material layer more firmly embedded in the coating interface, and can also reduce the charge transfer impedance while improving the pole piece peeling force, thereby improving the pole piece conductivity and reducing the battery DCR. In particular, when 0.05≤H2 / (H1+H2)≤0.15, the effect is more obvious, 40%≤H1≤50%, 1%≤H2≤10%, and H2 / (H1+H2)=0.1, the effect is better.

[0159] By comparing Example 1 and Example 16, it can be seen that the effects of silica sol and alumina sol are equivalent.

[0160] By comparing Example 1 and Comparative Example 3, it can be seen that the organic glue polyvinyl alcohol glue solution does not significantly improve the pinhole repair, and the electrode resistance is relatively large.

[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A current collector, characterized in that: It comprises a base layer, and a sol layer and a conductive layer sequentially arranged on at least one surface of the base layer; The sol layer includes an inorganic sol, and the inorganic sol includes at least one of aluminum sol, silica sol, silica-alumina sol, and phospho-alumina sol; The conductive layer includes a point-structured carbon material and a surface-structured carbon material.

2. The current collector according to claim 1, characterized in that: The surface density of the sol layer is G1, and the surface density of the conductive layer is G2, which satisfies: 4≤G2 / G1≤8.

3. The current collector according to claim 2, characterized in that: The mass percentage of the point-structured carbon material in the conductive layer is H1, and the mass percentage of the planar-structured carbon material in the conductive layer is H2, satisfying: 0.05≤H2 / (H1+H2)≤0.

15.

4. The current collector according to any one of claims 2 to 3, characterized in that: Satisfy at least one of the following (a) to (d): (a)0.1g / m 2 ≤G1≤0.3g / m 2 ; (b)0.5g / m 2 ≤G2≤2g / m 2 ; (c) 40% ≤ H1 ≤ 50%; (d)1%≤H2≤10%.

5. The current collector according to claim 1, characterized in that: Satisfy at least one of the following (e) to (h): (e) the average particle size of the inorganic sol is 1 to 50 nm; (f) the thickness of the sol layer is 0.1 to 1 μm; (g) the thickness of the conductive layer is 0.5 to 5 μm; (h) The thickness of the base layer is 5 to 20 μm.

6. The current collector according to claim 1, characterized in that: The oil absorption value of the point-structured carbon material is ≥120 mL / g; and / or The oil absorption value of the planar structure carbon material is ≥120 mL / g.

7. The current collector according to claim 1, characterized in that: The dot-structured carbon material includes at least one of conductive carbon black, Ketjen black and acetylene black; and / or The planar carbon material includes at least one of layered graphite and graphene.

8. The method for preparing a current collector according to claim 1, characterized in that: The following steps are involved: Applying the inorganic sol liquid on the surface of the substrate layer and drying it to form a sol layer; Then, a conductive paste is applied to the sol layer and dried to form a conductive layer; The conductive paste includes a point-structured carbon material and a surface-structured carbon material; The content of the inorganic sol in the inorganic sol solution is 0.4-1%.

9. A secondary battery, characterized in that: The present invention comprises the current collector according to any one of claims 1 to 7.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.